Privacy Preserving Healthcare System using secured cloud environment (International Journal of Engineering and Computer Science, 2017)
Wireless devices that used to measure physiological signals to help develop health management become increasingly popular in recent years.Records are conducive for follow-up health and medical care. Using different type of wireless devices and the factors of a large number ofusers, large number of data are lead to create a security threads and privacy problems. With the help of wireless technology and cloudcomputing we may solve the traditional way of problems occurred at the time of data management and data transmission in healthmanagement system. This healthcare management application to propose an integrated algorithm technique for the jointly involved partieswhich is included privacy and security algorithm; it can protect data integrity also. This system provides the better efficiency and it is veryuseful to remote areas where hospitals are not easily accessible. This research to resolve wireless sensor network security relevant issuesUsing several patterns can reduce database load, and users to access data efficiently; the privacy control mechanism allow users to storedata securely. The results of this research exhibit that the proposed system has better secured database access and maintain privacy for allpatient data than the traditional database.